URGENSI BIMBINGAN DAN PENYULUHAN (ISLAM) D ALAM PEMBANGUNAN KESEJAHTERAAN SOSIAL - Wiwit Widiansyah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2007)
World development and changes have many impacts to human beings. The changes happen almost in every aspect of life, including physical and nonphysical aspects. The physical changes includes means of communication, transportation, building facilities, agriculture, and many others. The other includes values and norms, tradition, mental attitude, family life pattem, work culture, daily life pattem, etc. These changes bring not only positive effects, but also negative ones to human beings. To increase social welfare, counseling has a significant role to solve social problems, especially in supporting education process and changing its target’s behavior.